(untitled) (Journal of Parents and Teachers, 2013)
The first years are the most intense, the most amazing and thrilling ones. At least, this is how she thinks so far. In this article, Esther shares her first professional experience in New York as an Elementary teacher: anecdotes, ideals and reflections that try to wake something up in her fellows and in all those who take a look at the last number of Padres y Maestros magazine.